2015
DOI: 10.1016/j.cmet.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

BMPR2 Preserves Mitochondrial Function and DNA during Reoxygenation to Promote Endothelial Cell Survival and Reverse Pulmonary Hypertension

Abstract: Summary Mitochondrial dysfunction, inflammation and mutant bone morphogenetic protein receptor (BMPR)2 are associated with pulmonary arterial hypertension (PAH), an incurable disease characterized by pulmonary arterial (PA) endothelial cell (EC) apoptosis, decreased microvessels and occlusive vascular remodeling. We hypothesized that reduced BMPR2 induces PAEC mitochondrial dysfunction, promoting a pro-inflammatory or pro-apoptotic state. Mice with EC-deletion of BMPR2 develop hypoxia-induced pulmonary hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
202
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(219 citation statements)
references
References 62 publications
15
202
1
1
Order By: Relevance
“…Neither IPAH/HPAH PAEC nor iPSC-EC showed a difference in cell growth when compared with control cells as judged by the WST-8 assay over 7 days in full-serum media (see Figure E5). As in our previous study changes in mitochondrial membrane potential could be detected without a change in proliferation (19).…”
Section: Results Ipsc-ec Have Typical Morphology and Functional Charasupporting
confidence: 81%
See 1 more Smart Citation
“…Neither IPAH/HPAH PAEC nor iPSC-EC showed a difference in cell growth when compared with control cells as judged by the WST-8 assay over 7 days in full-serum media (see Figure E5). As in our previous study changes in mitochondrial membrane potential could be detected without a change in proliferation (19).…”
Section: Results Ipsc-ec Have Typical Morphology and Functional Charasupporting
confidence: 81%
“…For example, differential methylation seems to explain the cell-specific expression of the superoxide dismutase, and the endothelial nitric oxide synthase genes (26,27). Other studies, however, have shown similarities in PAEC and systemic EC dysfunction studied in relation to loss of BMPR2 (19,28), and to PAH in general (29). Here, we provide evidence for the first time that IPAH/HPAH PAEC and iPSC-EC from the same individuals have similar functional impairment related at least in part to reduced BMPR2 and downstream signaling, and gene expression of COL4A2.…”
Section: Discussionmentioning
confidence: 99%
“…Reactivation of the developmental signaling pathways is often associated with abnormal lineage specification and disease pathology in adult tissues. Coordinated Wnt and BMPR2 signaling influence the proliferation and survival of endothelium and smooth muscle during angiogenesis as well as vascular remodeling of the pulmonary circulation (20)(21)(22). We therefore sought to determine how their coordinated signaling in resident lung ABCG2 + mesenchymal precursors regulates pulmonary microvascular homeostasis in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the inflammatory mediator TNF-α (19), and genetic deficiency of BMPR2 or TopBP1 (20,21) can both promote DNA damage and impair endothelial cell proliferation and survival. Recently, we demonstrated that oxidative stress caused by reoxygenation after hypoxia combined with BMPR2 deficiency induced a mitochondrial DNA deletion, elevated caspase-3/7 activity in PAECs, and impaired reversal of pulmonary hypertension (22).…”
Section: Introductionmentioning
confidence: 99%